2013
DOI: 10.1016/j.ijom.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue stability after segmental distraction of the anterior mandibular alveolar process: a 5.5 year follow-up

Abstract: Soft tissue changes were analysed retrospectively in 17 patients following distraction osteogenesis (DO) of the mandibular anterior alveolar process. Lateral cephalograms were traced by hand, digitized, superimposed, and evaluated at T1 (17.0 days), after DO at T2 (mean 6.5 days), at T3 (mean 24.4 days), at T4 (mean 2.0 years), and at T5 (mean 5.5 years). Statistical analysis was carried out using Kolmogorov-Smirnov test, paired t-test, Pearson's correlation coefficient, and linear backward regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…10,15,[18][19][20] In studies using cephalometric measurements, various reference planes were used to examine vertical and horizontal changes. 1,[20][21][22][23][24][25][26][27][28][29] Frequently used ones among these planes are Sella Nasion plane or the plane ±7 degrees angled to this plane 10,11,19,20,24,25,[30][31][32][33] and Frankfort horizontal 9,15,34 as the horizontal reference plane, and the planes drew from Nasion or Sella point to these planes as the vertical plane. 9,10,15,19,24,25,30,32,34 Frankfort horizontal was selected as an HRL, and the perpendicular to the HRL through the Porion point was taken vertical reference line.…”
Section: Discussionmentioning
confidence: 99%
“…10,15,[18][19][20] In studies using cephalometric measurements, various reference planes were used to examine vertical and horizontal changes. 1,[20][21][22][23][24][25][26][27][28][29] Frequently used ones among these planes are Sella Nasion plane or the plane ±7 degrees angled to this plane 10,11,19,20,24,25,[30][31][32][33] and Frankfort horizontal 9,15,34 as the horizontal reference plane, and the planes drew from Nasion or Sella point to these planes as the vertical plane. 9,10,15,19,24,25,30,32,34 Frankfort horizontal was selected as an HRL, and the perpendicular to the HRL through the Porion point was taken vertical reference line.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term soft tissue changes after AMSDO using a tooth-borne distraction device disclosed that the net effect of the soft tissue at point B is 88% of the total skeletal advancement at point B and the lower lip followed the advancement of incision inferior to 24% after 5.5 years [ 4 ]. The authors concluded that the physiological process of aging and loss of soft tissue elasticity should be considered as a reason for the soft tissue changes over time [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…On peut parfois éviter les extractions en envisageant le traitement autrement (Fig. 10) grâce à la distraction antéropos-térieure du segment frontal qu'elle soit maxillaire ou mandibulaire [4][5][6]9] (Figs. 11a, 11b) mais égale-ment grâce à la distraction transversale maxillaire (Fig.…”
Section: Sr : Pour Maintenir Ce Que Tu Appelles Le « Volume » C'esunclassified